Initial Impairment and Recovery of Vision-Related Functioning in Participants With Acute Optic Neuritis From the RENEW Trial of Opicinumab. Issue 2 (June 2019) - Petrillo, Jennifer; Balcer, Laura; Galetta, Steven; Chai, Yi; Xu, Lei; Cadavid, Diego
Abstract : Background: Leucine-rich repeat and immunoglobulin domain-containing Nogo receptor-interacting protein 1 (LINGO-1) is a key suppressor of oligodendrocyte differentiation and axonal remyelination and regeneration. This analysis evaluated the potential benefit of opicinumab, a human monoclonal antibody against LINGO-1, vs placebo on exploratory clinical endpoints of patient-reported vision-related functioning and high-contrast visual acuity (HCVA) in RENEW participants with acute optic neuritis (AON). Methods: Participants were randomized to 100 mg/kg opicinumab intravenous or placebo every 4 weeks (6 infusions). Assessments were conducted in the per-protocol (PP) population and included: 25-item National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25), 10-item Neuro-Ophthalmic Supplement (NOS-10), and HCVA. Results: The opicinumab group (n = 33) had worse mean (SD) baseline patient-reported vision-related functioning scores vs placebo (n = 36): NEI-VFQ-25 composite, 75.5 (17.6) vs 79.0 (16.6); NOS-10 composite, 63.6 (19.8) vs 69.8 (21.2), respectively. By Week 24, the placebo and opicinumab groups experienced substantial mean improvements from baseline (NEI-VFQ-25 composite, 15.17 vs 13.51 [difference (95% CI): −1.66 (−5.11 to 1.78)]; NOS-10 composite, 17.40 vs 16.04 [difference (95% CI): −1.35 (−7.38 to 4.67)]). Between-treatment differences in mean change from baseline were not significantly different at any time point. Analysis of covariance–adjusted mean recovery from baseline in HCVA at Week 24 for the affected eyes was 11.8 and 8.7 letters for placebo and opicinumab, respectively ( P = 0.202). Conclusions: Most participants in the RENEW PP population demonstrated substantial recovery from baseline in patient-reported vision-related functioning and HCVA, regardless of treatment and structural damage. Average scores after recovery remained lower than those of published disease-free control groups. These results provide important information on visual function recovery in patients with AON, as measured by NEI-VFQ-25 and NOS-10. Abstract : Supplemental Digital Content is Available in the Text.